Mesozooplankton Community Dynamics and Grazing Potential Across Algal Bloom Cycles in a Subtropical Estuary - Sweat, L. Holly; Alexander, Hunter; Phlips, Edward J.; Johnson, Kevin B. (Frontiers in Marine Science, 2021)
Mesozooplankton, as abundant grazers of microalgae in coastal systems, have the potential to prevent or mitigate harmful algal blooms (HABs) and their effects. The Indian River Lagoon (IRL) is a subtropical estuary in eastern Florida (USA) where repeated blooms, dominated by the toxic dinoflagellate Pyrodinium bahamense, the brown tide species Aureoumbra lagunensis, pico/nano planktonic cyanobacteria and other nano-eukaryotes, have highlighted the need to better understand fluctuations in the grazing potential of mesozooplankton populations across bloom cycles. Mesozooplankton and abiotic environmental data were collected at five sites in the northern IRL system at six-week intervals from November 2013 through June 2016. A total of 107 taxa from 14 phyla were detected. Communities varied across sites, dates and between bloom and non-bloom periods, with densities up to 338 individuals L-1. Eight taxa comprising 85 – 94% of the total population at each site were identified as primary potential grazers, including barnacle nauplii, cladocerans, adult copepods, gastropod veligers, larvaceans and polychaete metatrochophores. Although abundant, the estimated grazing potential of the primary taxa, calculated from their measured densities and previously published grazing rates, suggest that mesozooplankton lack the capacity to suppress phytoplankton once they reach bloom levels. These findings illustrate the utility of monitoring data and underscore the importance of systematically evaluating algal bloom controls with a consideration for the dynamic conditions of each unique ecosystem.